2016
DOI: 10.1186/s12883-016-0676-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual stimuli on standing posture in children with bilateral cerebral palsy

Abstract: BackgroundIn children with bilateral cerebral palsy (CP) maintaining a standing position can be difficult. The fundamental motor task of standing independently is achieved by an interaction between the visual, somatosensory, and vestibular systems. In CP, the motor disorders are commonly accompanied by sensory and perceptual disturbances. Our aims were to examine the influence of visual stimuli on standing posture in relation to standing ability.MethodsThree dimensional motion analysis with surface electromyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…These studies reported that children with CP demonstrated higher sway frequency and amplitude, especially when the vestibular system was required to maintain balance (i.e., unstable surface with eyes closed). 25,26,[29][30][31]36 One article 30 also showed that these results are significantly different in subgroups of CP, for example between children who required support and those who do not. Without extensive testing, clinicians would not know if the balance impairments experienced by children with CP, typically attributed to a poor neural drive, would be compounded by an aberrant vestibular and/or oculomotor system.…”
Section: Integration Of Vestibular Andmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies reported that children with CP demonstrated higher sway frequency and amplitude, especially when the vestibular system was required to maintain balance (i.e., unstable surface with eyes closed). 25,26,[29][30][31]36 One article 30 also showed that these results are significantly different in subgroups of CP, for example between children who required support and those who do not. Without extensive testing, clinicians would not know if the balance impairments experienced by children with CP, typically attributed to a poor neural drive, would be compounded by an aberrant vestibular and/or oculomotor system.…”
Section: Integration Of Vestibular Andmentioning
confidence: 99%
“…Four of these studies were from the United States, 6,[26][27][28] and three articles were from Brazil. 13,14,29 Greece, 9,10 Sweden, 17,30 United Kingdom, 31,32 and Belgium 33,34 each produced two articles, while Italy, 11 Turkey, 25 Iran, 35 Canada, 8 Israel, 15 and China 36 each produced one article. Nine articles examined oculomotor function in children with CP.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This sign has been defined as characteristic for perceptual disorders in children with spastic CP (Ferrari et al, 2014). Moreover, proprioception deficits in the lower limbs in children with CP have been associated with motor disturbances during standing and walking (Bartonek et al, 2018;Damiano et al, 2013;Lidbeck et al, 2016;Wingert et al, 2009) where in the latter study during turning gait, difficulties in spatial orientation was believed to negatively influence locomotion.…”
mentioning
confidence: 99%